Highly sensitive fusion detection using plasma cell‐free RNA in non‐small‐cell lung cancers. Issue 10 (18th August 2021) - Hasegawa, Nobuhiko; Kohsaka, Shinji; Kurokawa, Kana; Shinno, Yuki; Takeda Nakamura, Ikuko; Ueno, Toshihide; Kojima, Shinya; Kawazu, Masahito; Suehara, Yoshiyuki; Ishijima, Muneaki; Goto, Yasushi; Kojima, Yuki; et al.
Abstract: ALK, ROS1, and RET kinase fusions are important predictive biomarkers of tyrosine kinase inhibitors (TKIs) in non‐small‐cell lung cancer (NSCLC). Analysis of cell‐free DNA (cfDNA) provides a noninvasive method to identify gene changes in tumor cells. The present study sought to use cfRNA and cfDNA for identifying fusion genes. A reliable protocol was established to detect fusion genes using cfRNA and assessed the analytical validity and clinical usefulness in 30 samples from 20 cases of fusion‐positive NSCLC. The results of cfRNA‐based assays were compared with tissue biopsy and cfDNA‐based liquid biopsy (Guardant360 plasma next‐generation sequencing [NGS] assay). The overall sensitivity of the cfRNA‐based assay was 26.7% (8/30) and that of cfDNA‐based assay was 16.7% (3/18). When analysis was limited to the samples collected at chemo‐naïve or progressive disease status and available for both assays, the sensitivity of the cfRNA‐based assay was 77.8% (7/9) and that of cfDNA‐based assay was 33.3% (3/9). Fusion gene identification in cfRNA was correlated with treatment response. These results suggest that the proposed cfRNA assay is a useful diagnostic test for patients with insufficient tissues to facilitate effective administration of first‐line treatment and is a useful tool to monitor the progression of NSCLC for consideration of second‐line treatments. Abstract : cfRNA‐ and cfDNA‐based assays are evaluated in 20 cases of fusion‐positive NSCLC. cfRNA assay was superior to cfDNA assay for the detection of gene fusions. The results of the cfRNA assay were consistent with the therapeutic effect.